POTENTIAL AND CHALLENGES OF UTILIZING FAMILY YARDS TO SUPPORT EDUCATION-BASED FOOD SECURITY - Efendi, Burhan; Susanti; Syahriza, Muhammad; Maryam (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
The utilization of home gardens has significant potential to support household food security while serving as a medium for ecological and family-based education. This study aimed to describe the conditions of yard utilization, analyze family perceptions and attitudes, and identify the practices and challenges faced in their management. A descriptive quantitative–qualitative approach was employed involving 30 families in Mojogedang District, Karanganyar. Data were collected through observation, interviews, and a five-point Likert-scale questionnaire measuring yard size and function, cultivation skills, motivation level, family participation, and support for children’s involvement. The data were analyzed descriptively to explore the relationships between physical yard conditions, family perceptions, and management constraints. The results show that most families own yards measuring 50–100 m² (40%), exhibit high motivation for productive use (80% agree–strongly agree), and express full support for involving children in yard activities (100% agree–strongly agree). The main challenges include limited cultivation skills, lack of production inputs, and time constraints for management. This study recommends the development of the Rumah Pangan Berkemajuan (RPB) Model based on four pillars: technical strengthening, integration of family education, socio-economic networking, and religious–ecological values. These findings provide a conceptual foundation for yard management oriented toward sustainable food security and ecological family character education.